2014
DOI: 10.1074/jbc.m113.515866
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Membrane Disruption by Cytotoxic Amyloid Oligomers Formed by Prion Protein(106–126) Is Dependent on Bilayer Composition

Abstract: Background: Nonfibrillar amyloid oligomers are cytotoxic and may act through physical disruption of cell membranes. Results: Cytotoxic oligomers of the amyloid peptide PrP(106 -126) disrupt membranes through distinct mechanisms, depending on lipid composition. Conclusion: Cytotoxicity of PrP(106 -126) oligomers can occur through at least two different physical processes. Significance: Mechanisms for the membrane disruption of amyloid oligomers are proposed, providing new insight into their cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 81 publications
2
62
0
Order By: Relevance
“…For instance, oligomerized prion was shown to disturb anionic phospholipid membrane through a detergent model in which the membrane leakage is caused by the removal of lipid-prion micelles. In contrast, prion oligomer accumulation on the cholesterol containing zwitterionic liposomes was shown to induce a loss of raft domains, which destroys membrane integrity (49). The physical basis for PB1-F2 membrane disruption remains to be elucidated, but our results suggest PB1-F2 lysis activity is related to the protein oligomers.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For instance, oligomerized prion was shown to disturb anionic phospholipid membrane through a detergent model in which the membrane leakage is caused by the removal of lipid-prion micelles. In contrast, prion oligomer accumulation on the cholesterol containing zwitterionic liposomes was shown to induce a loss of raft domains, which destroys membrane integrity (49). The physical basis for PB1-F2 membrane disruption remains to be elucidated, but our results suggest PB1-F2 lysis activity is related to the protein oligomers.…”
Section: Discussionmentioning
confidence: 54%
“…For instance, it was shown that Shadoo, ␣-synuclein, and the type 2 diabetes-associated islet amyloid polypeptide extensively damage the membrane when they start to aggregate because their growing entities capture and extract lipids from the bilayer (44, 46 -48). One amyloid protein may, also, employ different mechanisms to interact with membranes depending on the membrane lipid composition (49). For instance, oligomerized prion was shown to disturb anionic phospholipid membrane through a detergent model in which the membrane leakage is caused by the removal of lipid-prion micelles.…”
Section: Discussionmentioning
confidence: 99%
“…Matej et al (2012) have reported direct involvement of protease-activated receptors in prion-mediated responses [41]. Both PrP(106-126) and A␤ [25][26][27][28][29][30][31][32][33][34][35] have also been shown to interact with plasma membrane of cells [42][43][44][45][46]. PrP(106-126) preferentially binds with lipid raft-like structures on cell membranes [47], which could facilitate calcium mobilization from extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms of toxicity include prion oligomer membrane insertion as pores or channels, similar to A␤ in Alzheimer's disease pathology (47,48); detergent-like activity, similar to islet amyloid precursor protein in diabetes pathology (49); and prion fibrillization on the surfaces of lipid rafts, leading to a functional loss of membrane domain organization (50). These toxic interactions appear to depend on the composition of the lipid bilayer.…”
Section: Figmentioning
confidence: 99%
“…The ability of amyloid-␤ to form pores and fragment lipid bilayers depends on the presence of gangliosides (48). Studies altering the content of anionic cellular membrane lipids induced a switch in prion oligomer membrane interactions from micelle formation to increased formation of fibrils on lipid microdomains (50). Membrane lipids, specifically PE, have been shown to act as a cofactor in prion protein conversion in vitro by facilitating protein structural changes (10,51).…”
Section: Figmentioning
confidence: 99%